2019
DOI: 10.1098/rspb.2019.1089
|View full text |Cite
|
Sign up to set email alerts
|

Cilia drive developmental plasticity and are essential for efficient prey detection in predatory nematodes

Abstract: Cilia are complex organelles involved in a broad array of functions in eukaryotic organisms. Nematodes employ cilia for environmental sensing, which shapes developmental decisions and influences morphologically plastic traits and adaptive behaviours. Here, we assess the role of cilia in the nematode Pristionchus pacificus, and determine their importance in regulating the developmentally plastic mouth-form decision in addition to predatory feeding and self-recognition behaviours, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The presence of teeth in P. pacificus facilitates an additional behavior as they are capable of predating the larvae of other nematodes. Here, it has been observed that the mouth-form dimorphism strongly correlates with the predation behavior, as only the morphs possessing two teeth are active predators, whereas the single-toothed morphs are strict bacterial feeders ( Wilecki et al 2015 ; Moreno et al 2019 ; Akduman et al 2020 ). Furthermore, the predatory behavior coincides with the existence of a self-recognition system ( Lightfoot et al 2019 ) and environmental responses distinct from C. elegans ( Hong and Sommer 2006 ; Moreno et al 2016 , 2017 ).…”
mentioning
confidence: 91%
“…The presence of teeth in P. pacificus facilitates an additional behavior as they are capable of predating the larvae of other nematodes. Here, it has been observed that the mouth-form dimorphism strongly correlates with the predation behavior, as only the morphs possessing two teeth are active predators, whereas the single-toothed morphs are strict bacterial feeders ( Wilecki et al 2015 ; Moreno et al 2019 ; Akduman et al 2020 ). Furthermore, the predatory behavior coincides with the existence of a self-recognition system ( Lightfoot et al 2019 ) and environmental responses distinct from C. elegans ( Hong and Sommer 2006 ; Moreno et al 2016 , 2017 ).…”
mentioning
confidence: 91%
“…Kin discrimination in this system largely depends on the identity of a hypervariable small peptide that is expressed in the nematodes’ body-wall epidermis (Lightfoot et al, 2019 ) and, otherwise, on overall genetic relatedness (Lightfoot et al, 2021 ). Although the cilia of anterior sensilla are required for prey assessment and environmental sensing in P. pacificus , self-recognition does not seem to require fully functioning cilia (Moreno et al, 2019 ), so it is not yet known how the peptide signal and genetic identity of others is detected.…”
Section: Identification and Evolution Of Environmental Sensing Mechan...mentioning
confidence: 99%
“…Similar to C. elegans, the reproductive system of P. pacificus is hermaphroditic, and its genome has been sequenced (Dieterich et al, 2008), allowing CRISPR/Cas9 genome editing (Witte et al, 2015). Using this system, many mutants have been generated and analyzed to understand the molecular mechanisms of various phenomena, such as phenotypic plasticity (Moreno et al, 2019;Namdeo et al, 2018;Ragsdale & Ivers, 2016;Serobyan et al, 2016;Sieriebriennikov et al, 2017Sieriebriennikov et al, , 2018Sieriebriennikov et al, , 2020, feeding behaviors (Ishita et al, 2021;Okumura et al, 2017), self-recognition (Lightfoot et al, 2019), dauer development (Markov et al, 2016), and sensory systems (Carstensen et al, 2021;Moreno et al, 2017Moreno et al, , 2018Moreno et al, , 2019. Using CRISPR/Cas9 genome editing, the molecular mechanisms of these interesting characteristics of P. pacificus have been revealed to promote our understanding of developmental biology, neurobiology, and evolution.…”
Section: Backg Round and Fe Ature Smentioning
confidence: 99%